Analisis Pengaruh Beban Pajak Dan Tunneling Incentive Terhadap Transfer Pricing : Studi Pada Perusahaan Multinasional Terdaftar Di Bursa Efek Indonesia - J Surono (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2023)
Transfer Pricing is the price that contained on every single product or service that transferred from one division to another division of the company or inter related companies. But time by time, more companies are doing transfer pricing. The purpose of this research is to analyze the influence of tax expense, tunneling incentive and bonus plan on transfer pricing on multination companies. The populations of this research are multinational companies in 2017. The samples are selected using purposive sampling method, and obtained 90 unit of analysis as observations object. The analysis tool is logistic regression with SPSS 21.The result shows that tax expense has significant effect on transfer pricing. While tunneling incentive and bonus plan has no significant effect on transfer pricing. The conclusion of this research is one percent increase on tax expense will decrease the result of transfer pricing. Suggestions for the next research is the researcher should use a longer time vulnerable to get better result.